Perancangan Antena Segitiga Gerigi Circular Slot untuk Aplikasi Long Term Evolution (LTE) - Eriane Putri, Febby; Charisma, Atik; Ketut Hariyawati Dharmi, Ni (ELECTRON Jurnal Ilmiah Teknik Elektro, 2021)
The communication technology that is currently popular is 4G LTE technology. Technology that has very high efficiency and speed of access. Antennas with good performance are needed to support LTE technology with small dimensions, light weight and cheap to manufacture in large quantities, and these antennas are microstrip antennas. Microstrip antenna has the disadvantage of low gain and narrow bandwidth. Proximity coupled is one method to improve bandwidth and gain on microstrip antennas. Proximity coupled is a feeding technique or method of feeding by adding a substrate for the groundplane and feed channel. In this simulation, in addition to using the proximity coupled feeding method, the patch antenna which is triangular in shape will be added to a circular slot to improve the performance of the antenna. The simulation results obtained for the resonant frequency of 2.35 GHz, namely return loss -24.6419 dB, VSWR 1.0192 and gain 6.6598 dB and bandwidth of 73.3 MHz with range 25 – 100 MHz. This specification is in accordance with the needs of LTE antennas